Konseling Keluarga dalam Persepektif Fiqih Sosial - Saifurrijal, Nur Muhammad (CV. Lentera Literasi Indonesia, 2025)
This study aims to examine the concept of family counseling from the perspective of social fiqh as a solution-oriented approach to household problems in modern Muslim society. Family counseling in Islam does not only function as a means of solving psychological or relational problems, but also as a medium for strengthening spiritual values ​​and Islamic law in household life. This study uses a descriptive qualitative method with a library research approach, which explores the views of relevant figures and theories, such as the thoughts of Ali Yafie and Sahal Mahfudh on social fiqh, as well as Islamic counseling theories. The results of the study indicate that social fiqh provides a methodological and applicative basis for addressing family problems with a contextual, responsive approach, and based on maqāṣid al-syarī’ah values. Family counseling from this perspective becomes an integrative effort between divine guidance and social reality that aims to create a family that is sakinah, mawaddah, and rahmah, as well as prosperous physically and mentally. This study recommends that the concept of social fiqh be more mainstreamed in the development of Islamic family counseling services in various educational, social, and religious institutions.